METODE PENDIDIKAN RIHLAH DALAM PERSPEKTIF AL-QUR’AN: Perjalanan Pencarian Ilmu Nabi Musa A.S Kepada Nabi Khidhir A - Akso, Akso (Moderation | Journal of Islamic Studies Review, 2023)
The rihlah method (the journey of dispensing knowledge) of the struggle of the Prophet Musa inlearning from the Prophet Khidhir after receiving questions from his people, namely the children of Israel.The question is: Who is the most pious (smart) person in this world, O Musa?, Prophet Musa replied, I(Prophet Musa). Then Allah reminded Prophet Musa that the most pious person in the world was Khidir.Prophet Musa asked Allah, how should I meet him I do not know. Allah informed the Prophet Musa,that the person was at the confluence of two seas. Then Prophet Musa was told to take the fish on the way(rihlah) to go to that place, so when the fish goes out to a place, that is where Khidir is. The Prophet Musahad a great will to find Khidir, until he said I had to go on until whenever I had to meet God's servantwhose name was Khidir. This paper examines the rihlah method, namely how the Prophet Musa (as)traveled in search of knowledge by using the rihlah, namely making a tiring journey to meet a teacher. Atthat time the Prophet Musa received a revelation to seek knowledge from a servant of Allah whose locationand area were not known, he was only told the sign and address of the meeting of the two seas, so he made adifficult journey to find a teacher. This is explained in QS. Al-Kahfi (18): 60-82.